An orbital solitary fibrous tumor: report of two cases with different presentation - Hanisah AH,; Othmaliza Othman,; Rona Asnida Nasaruddin,; Sunder R,; Hazlita Mohd Isa, (Faculty of Medicine, Universiti Kebangsaan Malaysia Medical Centre, 2016)
Solitary fibrous tumour (SFT) is a rare spindle-cell neoplasm that can occur in the orbit. We report two cases of orbital SFT in a 35-year-old female and a 28-year-old male with different presentations. First patient presented with slowly progressive left lateral upper lid mass which is firm in consistency and non tender. Patient had non axial proptosis as the mass compressed the globe inferonasally. There was also funduscopy evidence of choroidal folds superotemporally. There is slight impairment of vision on the left eye comparing to right eye. Meanwhile, the second patient presented with a painless diffuse swelling of left upper eyelid. It was soft in consistency, non fluctuate and no opening or pus discharge noted. There is mild mechanical ptosis, however there was no proptosis and no evidence of compression into the globe nor visual impairment.Computed tomography (CT) imaging revealed a well circumscribed and contrast enhanced soft tissue mass intraorbital extraconal mass in both cases. However in the first case, the tumour was at the level of lacrimal gland with compression of the globe, while in second case, it was superior and posterior to the left lacrimal gland with no globe compression. Both patients underwent complete resection of their tumors. The histological findings showed alternating hypercellular and hypocellular areas composed of bland spindle cells with a fibrous stroma. The strong immunoreactivity for CD34 supported the diagnosis of orbital SFT. There was no recurrence at the 2nd and 3rd year follow-up visits for both patients. SFT should be considered as one of the differential diagnosis of an orbital tumor. The combination of CT scan, histologic findings and immunohistochemical staining provide accurate diagnosis. En bloc excision of the tumour is the mainstay of treatment.